2008
DOI: 10.1021/jp077471t
|View full text |Cite
|
Sign up to set email alerts
|

Generalized One-Pot Synthesis, Characterization, and Photocatalytic Activity of Hierarchical BiOX (X = Cl, Br, I) Nanoplate Microspheres

Abstract: A general one-pot solvothermal process was explored to prepare BiOX (X = Cl, Br, I) powders by employing ethylene glycol as the solvent. The as-prepared BiOX powders were characterized by X-ray powder diffraction, scanning electron microscopy, transmission electron microscopy, high-resolution transmission electron microscopy, UV−vis diffuse reflectance spectroscopy, and nitrogen sorption. The resulting BiOX samples were phase-pure and of hierarchical microspheres consisting of nanoplates. The band gaps of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
674
3
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 1,154 publications
(708 citation statements)
references
References 32 publications
24
674
3
7
Order By: Relevance
“…7a), indicating that the BiOBr is an excellent visible − light-response photocatalyst, as reported earlier. Again, no degradation of SA is observed in the BiOI system under either visible-light and UV irradiation, which is different from the results in previous reports (Chang et al, 2010;Qin et al, 2013;Zhang et al, 2008b), where it was reported that BiOI had the highest activity among BiOXs. Considering the narrow band gap and strong visible light absorption of BiOI, its inactivity in photocatalytic degradation is somewhat striking in our study.…”
Section: Characterization Of Bioxscontrasting
confidence: 99%
See 4 more Smart Citations
“…7a), indicating that the BiOBr is an excellent visible − light-response photocatalyst, as reported earlier. Again, no degradation of SA is observed in the BiOI system under either visible-light and UV irradiation, which is different from the results in previous reports (Chang et al, 2010;Qin et al, 2013;Zhang et al, 2008b), where it was reported that BiOI had the highest activity among BiOXs. Considering the narrow band gap and strong visible light absorption of BiOI, its inactivity in photocatalytic degradation is somewhat striking in our study.…”
Section: Characterization Of Bioxscontrasting
confidence: 99%
“…Qin and their coworkers (Qin et al, 2013) found that 2-methoxyethanol could help BiOCl and BiOBr construct into even hierarchical architectures, while the same type of BiOI could not be obtained under otherwise identical reaction conditions unless ethylene glycol was substituted for 2-methoxyethanol. Ethylene glycol was always used in the formation of hierarchical microspheres (Zhang et al, 2008b(Zhang et al, , 2011, and glycols tended to help obtain more compact, dense and larger catalyst particles compared with those synthesized with ethanol. In order to determine the effect of solvent, we also synthesized BiOBr-EG using ethylene glycol instead of ethanol under otherwise identical conditions, and BiOBr-H 2 O with a hydrothermal method according to previous work of our laboratory (Wang et al, 2012).…”
Section: Active Species Analysismentioning
confidence: 99%
See 3 more Smart Citations